2021
DOI: 10.1007/s10854-021-06158-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ga doping for non-stoichiometric sodium bismuth titanate ceramics

Abstract: The electrical performance of Ga 3+ doping Na0.5Bi0.5TiO3-based oxygen ion conductor was studied. The Na0.52Bi0.47Ti1-xGaxO3-δ (x=0, 0.01, 0.015, 0.02) samples were fabricated by the means of traditional solid-state reaction. The results of AC impedance measurement show that the bulk conductivity of Na0.52Bi0.47Ti1-xGaxO3-δ samples decrease monotonously with the increase of Ga 3+ doping. At 673 K, the bulk conductivity of the Na0.52Bi0.47Ti0.98Ga0.02O3-δ sample is 7.19×10 -4 S/cm, which is lower than that of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Bhattacharyya et al [12] incorporated Mg 2+ to highly nonstoichiometric Na 0.54 Bi 0.46 TiO 3-δ and obtained the highest σ b by 1% Mg doping. The phenomenon that there exists an optimum doping level, above which σ b decreases with increasing doping level, has been widely observed in NBT with other B-site dopants such as Ga 3+ , Al 3+ , Sc 3+ , and Fe 3+ [8][9][10]15,16]. The limited enhancement of σ b by B-site acceptor doping was first explained by He and Mo by first-principles calculations [22].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bhattacharyya et al [12] incorporated Mg 2+ to highly nonstoichiometric Na 0.54 Bi 0.46 TiO 3-δ and obtained the highest σ b by 1% Mg doping. The phenomenon that there exists an optimum doping level, above which σ b decreases with increasing doping level, has been widely observed in NBT with other B-site dopants such as Ga 3+ , Al 3+ , Sc 3+ , and Fe 3+ [8][9][10]15,16]. The limited enhancement of σ b by B-site acceptor doping was first explained by He and Mo by first-principles calculations [22].…”
Section: Introductionmentioning
confidence: 97%
“…In 2014, a new family of oxide ion conductors based on the ferroelectric perovskite sodium bismuth titanate (Na 0.5 Bi 0.5 TiO 3 , NBT) was reported [1]. Since then, numerous efforts have been devoted to enhancing the bulk conductivity (σ b ) of NBT by introducing A-site cation nonstoichiometry and/or acceptor doping [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], based on which the following cognitions have been established: (1) high oxideion conductivity can be obtained in Na-rich or Bi-deficient NBT, e.g., Na 0.51 Bi 0.5 TiO 3.005 (N 0.51 BT) or Na 0.5 Bi 0.49 TiO 2.985 (NB 0.49 T) [2]; (2) acceptor doping, either on A-site (e.g., partial replacement of Bi 3+ by Sr 2+ [3]) or B-site (e.g., partial substitution of Ti 4+ by Mg 2+ [1]), generates oxygen vacancies by an ionic compensation mechanism, and therefore is an effective approach for enhancing the σ b of NBT [8]; (3) σ b of acceptor-doped NB 0.49 T is higher than that of yttria-stabilized zirconia (YSZ) at < 600 • C, and it shows no appreciable degradation at 500 • C contrary to the rapid conductivity decay for rare-earth-stabilized δ -Bi 2 O 3 [6], which makes NBT-based oxide ion conductors promising candidate electrolyte materials for IT-SOFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on understanding the role of structural defects in the form of oxygen vacancies in the electrode material has shown substantial improvement in the electrochemical performance of supercapacitors [18]. Researchers found that point defects, particularly oxygen vacancies, led to increased capacitance and decreased impedance of the electrode material in perovskite ceramics [19][20][21]. Interestingly, it was also experimentally reported that point defects in graphene oxide-based electrodes, such as oxygen-containing functional groups and vacancies, led to the same effect on the capacitance and impedance of the electrode material [22][23][24].…”
Section: Introductionmentioning
confidence: 99%